An Analysis of Derivational Suffixes Used in @Wetheurban Instagram Posts - Sari, Luh Devi Puspa; Artawa, Ketut; Indrawati, Ni Luh Ketut Mas (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2023)
The title of this research is "An Analysis of Derivational Suffixes Used in @Wetheurban Instagram Posts." The purpose of this research was to identify the forms of derivational suffixes and explain their function and meaning used in Instagram posts by @Wetheurban. The data for this research was derived from Instagram posts by @Wetheurban, which created this Instagram to increase personal power by 1000%.The data was collected by reading and highlighting the Instagram account @Wetheurban. The data for this study was analyzed qualitatively. This study used Plag's (2002) theory from his book "Word -Formation in English". The analysis showed four types of derivational suffixes: 14 nominal suffixes, 2 verbal suffixes, 10 adjectival suffixes, and 2 adverbial suffixes. Derivational suffixes have two functions: class-maintaining suffixes and class-changing suffixes. Suffixes found in the data source each have their own meaning, such as person or having something to do with X, result of X, state or quality, tending to, connected with, and so on.